Cloning and analysis of genome of transmissible gastroenteritis virus SC-Y strain - SONG Zhen-hui; GUO Wan-zhu; YIN Hua-ping (浙江大学学报. 农业与生命科学版)
Sixteen pair of primers covering the whole genome of TGEV were devised according to the published sequences, 16 cDNA fragments were amplified by RT-PCR. The amplified fragments were further cloned and sequenced. The genome of SC-Y strain was assembled by BioEdit (GenBank: DQ443743). The size of complete genome was 28590 nucleotides (including Poly A), and was comprised of 7 ORFs, which was flanked by untranslated regions (UTRs), 315 bases at the 5'-end and 277 bases at the 3'-end. there were 6 nt deletions in S genes compared with that of the other isolates, Miller M60, Miller M6 and TS. Phylogenetic analysis based on S, sM, M and N suggested that SC-Y may belong to same genogroup with purdue strain. TGEV SC-Y has slightly bias at the codons which are T and A at the end. Yeast system should be more suitable for TGEV' gene expression.